Governing through Controversy: The Challenge of New Toxicological Methodologies. Issue 3 (26th September 2022) - Ellis, Jaye
Abstract: Building institutional and procedural bridges between science and policy is a vital role for law. Fundamental to the success of this work is the development of more sophisticated, nuanced understandings of scientific knowledge production than those which are current in legal and policy spheres. In this paper, I consider scientific controversies that have emerged in the field of human and environmental health impacts of endocrine disrupting chemicals (EDCs), notably around methodological approaches to identifying such chemicals and analysing the risks they pose. Building on literatures in the philosophy and sociology of science, I identify bases on which bridge-building between science and policy could proceed and discuss the role that legal normativity can play in those processes.